The Effect of Good Corporate Governance, Internal Audit, And Whistleblowing System on Fraud: Empirical Study on State-Owned Enterprise Companies Listed on the Indonesia Stock Exchange for the 2017 – 2021 Period - Rahmawati, Oktaviani; Meini, Zumratul; Digdowiseiso , Kumba (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2023)
This research aims to analyze and obtain empirical evidence of the influence of Good Corporate Governance, Internal Audit, and Whistleblowing Systems on the occurrence of Fraud in State-Owned Enterprise companies listed on the Indonesia Stock Exchange for the 2017-2021 period. This study used secondary data obtained from the IDX.co.id website. The population in the study is 23 State-Owned Enterprise companies listed on the Indonesia Stock Exchange for the 2017-2021 period. The sample used uses the purposive sampling method. The analysis method used logistic regression and IBM SPSS Statistics software program version 25. The results of this study show that the variable Good Corporate Governance (X1) has a negative and insignificant effect or Good Corporate Governance does not affect the occurrence of Fraud. While the Internal Audit Variable (X2) and Whistleblowing System (X3) have a positive and significant effect on the occurrence of Fraud.